Tanah Ulayat Dalam Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Aquinta Welly Wenno; Jemmy Jefry Pietersz; Jenny Kristiana Matuankotta (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Land acquisition is the act of transferring land by paying proper and fair compensation to the rightful party. The problems of indigenous peoples regarding the use of their customary lands are used for the development of public interests and should have an important role in the procurement process up to the compensation they must receive as a form of legal protection. Realization of development land acquisition for public interest and its implementation stages are guided by Government Regulation Number 19 of 2021 concerning Land Procurement for Public Interest. The government has the authority to organize land acquisition for development in the public interest. This research is to answer the problems of indigenous peoples regarding the use of their customary land which is used for the development of public interests and should primary, secondary and tertiary legal materials. The results of this study indicate that the realization of development land have an important role in the procurement process up to the compensation they must receive as a form of legal protection. Which uses a normative-juridical method with the Statute Approach approach. , and Conceptual Approach as well as using acquisition for the public interest and the stages of its implementation are guided by Government Regulation Number 19 of 2021.